SAT0213 Is Acoustic Radiation Force Impulse (ARFI) Quantification A Useful Noninvasive Method for Assessing Salivary Glands?. (10th June 2014) - Guerin, A.; Saraux, A.; Cornec, D.; Gestin, S.; Bressollette, L.; Diallo, I.; Devauchelle-Pensec, V.; Quehe, P.; Marhadour, T.; Jousse-Joulin, S.
Abstract : Background: The ARFI method is a new tool to evaluate the stiffness of soft tissues which is is wellknown for evaluating the stiffness of liver parenchyma. No studies have been done concerning the salivary glands parenchyma. Objectives: The aim of this study was to evaluate the ARFI method as a new tool to assess the stiffness of major salivary glands tissue. For this, we studied: 1. ARFI system in major salivary glands in healthy population depending on age and sex. 2. The intra and inter-observer reliability of ARFI quantification in major salivary glands in this population. Methods: We prospectively studied 30 healthy adults without known salivary pathology. We divided the population in 3 sub groups of age (15-30, 31-45, and 46-60 years old). ARFI quantification, given as shear waves velocity (SWV) of the 2 parotid and 2 sub-mandibular glands was performed by two observers (A.G, S.J.J). We used a SIEMENS S2000 machine with a linear probe (10-12.5 MHz frequency). We assessed the 2 parotids glands in a longitudinal scan and the 2 submandibular glands in a longitudinal scan. We realised 10 pulses for each glands. 5 pulses were done in the central part of the gland and the 5 others pulses were done in a superficial part. For statistical analysis, we calculated the average measures of the 10 pulses of each gland for each ultrasonographists. For reliability, we evaluated the intra class coefficient correlation. Results: The average parotid and sub-mandibular SWV were in m/sec 1.9 and 1.99 for men (n=15) and 1.78 and 1.77 for women (n=15), respectively. Parotid and sub-mandibular glands SWV were 1.81 and 1.78 for the 15-30 years old, 1.79 and 1.95 for the 30-45 years old and 1.93 and 1.9 for the 45-60 years old, respectively. Inter-observer agreement, expressed as intraclass correlation coefficient was not so good for the parotid and good for the sub-mandibular. Intra-observer agreement was respectively for observer A and B, 0, 613 and 0, 201 for the parotid and 0, 725 and 0, 594 for the sub-mandibular glands. Conclusions: ARFI method in salivary glands do not seem significantly different depending on age and sex in a healthy population. However, at this time, ARFI quantification needs to obtain a good reliability to be used in practice and to be evaluated in a population of primary GougerotSjögren Syndrome. References: Sporea I, Sirli R, Bota S, Vlad M, Popescu A, Zosin I. ARFI elastography for the evaluation of diffuse thyroid gland pathology: Preliminary results. World J Radiol. 2012 Apr 28;4(4):174-8. Acknowledgements: The team of radiology department and the team of Ultrasound Unit department from Brest, FRANCE Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4182